Urban green rating systems: Insights for balancing sustainable principles and heritage conservation for neighbourhood and cities renovation planning. (June 2022) - Lucchi, E.; Buda, A.
Abstract: The paper presents an overview of existing urban sustainability rating tools for their possible application in historic urban environments, facing the debate between environmental sustainability and urban heritage conservation. This critical study focuses on Urban Green Rating Systems (UGRS) that make a transparent and systematic decision-making support tool for evaluating the sustainability in urban planning, combining environmental, economic, and social aspects. The research aims at comparing different UGRS approaches for cities and neighbourhood renovation, highlighting main themes, criteria, indicators, pros, and cons to balance heritage preservation and sustainable development. All the UGRS give high importance to environmental aspects while lower or no consideration is dedicated to heritage conservation. Thus, gaps in the methodological approaches to be addressed in the future have been identified, to serve as a guideline and reference for developing a comprehensive, international assessment system to bridge this knowledge and applicability gap. Highlights: Debate between environmental sustainability and urban heritage conservation. Overview of existing protocols, tools and system for urban renovation assessment. Critical analysis and comparison of heritage conservation in existing Urban Green Rating Systems (UGRS). Themes, criteria, indicators, pros, and cons for balancing heritage preservation and sustainable development in UGRS. Suggestions for a new URGS on sustainability evaluations of urban heritage.